Assimilation of coastal and open sea biogeochemical data to improve phytoplankton simulation in the Mediterranean Sea. (December 2018) - Teruzzi, Anna; Bolzon, Giorgio; Salon, Stefano; Lazzari, Paolo; Solidoro, Cosimo; Cossarini, Gianpiero
Highlights: Variational assimilation of coastal and open sea satellite chlorophyll is proposed. Validation against in situ data shows benefits of coastal assimilation. Assimilation can compensate for model weakness in simulating coastal processes. A full basin estimation of primary production in the Mediterranean Sea is provided. Abstract: The high spatial and temporal variability of biogeochemical features, induced by local dynamics and terrestrial and atmospheric inputs in shelf seas, are challenging issues for the implementation of data assimilation in these areas. The objective of this study is to integrate satellite ocean-colour observations with a coupled physical-biogeochemical model in order to improve the spatiotemporal descriptions of chlorophyll and other biogeochemical variables in the Mediterranean shelf seas. We adopted a specifically developed three-dimensional variational data assimilation scheme for the assimilation of satellite chlorophyll data. The non-homogeneous vertical component, the non-uniform and direction-dependent horizontal component of the background error covariance are the key features of the upgraded three-dimensional variational data assimilation scheme for shelf seas. The application of the new assimilation scheme significantly improves chlorophyll estimates in shelf seas, particularly in the representation of their spatial and temporal variability. Based on these results, we provide an estimate of the annual primary production of the Mediterranean basin.